HUBUNGAN MUTU PELAYANAN KEPERAWATAN TERHADAP KEPUASAN PASIEN LANSIA POLI PENYAKIT DALAM - R.A. Fadila; Endang Sulastri (Jurnal Kesehatan dan Pembangunan, 2023)
Patient satisfaction is still a problem in several hospitals in Indonesia and even the world. Service qualityNursing as an indicator of the quality of health services is one of the determining factors for the image of health care institutions in the eyes of the public. The aim is to determine the relationship between the quality of nursing services and the satisfaction of elderly patients. This type of quantitative research uses relationships through a cross sectional approach, using analytic descriptions. The population is elderly polyclinic patients in internal medicine at the Siti Fatimah Hospital in South Sumatra Province in 2023, the sample size is 44 respondents. Determining the respondents by accidental sampling technique, data collection was carried out by means of a questionnaire which was then analyzed by statistical tests using the chi square test with α = 0.05. Those who get poor service quality and are not satisfied are 29.5% with a total of 13 respondents. Good service quality and satisfaction of 45.5% with a total of 20 respondents. Obtained a ρ value of 0.002 with a strong level of closeness. Based on the results of statistical tests using the chi square test ρ value 0.002 < α = 0.05 then Ho is rejected and H1 is accepted. There is a relationship between service quality and patient satisfaction in internal medicine polyclinics at Siti Fatimah Hospital. It is hoped that the quality of hospital services will be improved again, especially in the five quality indicators so that patients feel satisfied with the services they receive.